Barriers for people who inject drug (PWID) to access voluntary counselling and testing (VCT) at the health centres in East Lombok - Dany Karmila; Pande Putu Januraga; Ni Wayan Septarini (Universitas Udayana, 2017)
Background and purpose: Utilisation of voluntary counselling and testing (VCT) by people who inject drug (PWID) in East Lombok is low. This study aims to explore barriers for PWID to access VCT service from community health centres in East Lombok, West Nusa Tenggara. Methods: A qualitative study was conducted in East Lombok. Data were collected using in-depth interviews. Nine participats were purposively selected consisted of five HIV negative PWID who repeatedly tested for HIV, one non-governmental organization official, one field worker, one VCT counsellor and one medical doctor. Data were inductively analysed. Results: This study found that PWID preferred to use mobile VCT rather than VCT at health centres because of scared of getting caught by police. They also felt uncomfortable of using VCT service at the health centres due to stigma and discrimination. In addition, lack of human resources at the health centre was also found to be a significant barrier. This led to increased workload thus limited attention was given to quality of VCT service. Conclusions: Barriers to access VCT service at the health centre include high stigma and discrimination from health provider and living arrangements of PWID. To improve VCT access for PWID, effective collaboration between health centres, private health institutions and village cadres are required.